Overview of Halal Cosmetics in a Decade: A Bibliometric Analysis - Wan Suryani; Irwan Mohd Subri; Ahmad Rafiki; Fitriani Tobing; Sutan Emir Hidayat (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
This article applies bibliometric analysis to examine existing works and literature on Halal Cosmetics to explore the concept’s evolving journey since its emergence. This study applies bibliometric approaches such as citation, co-citation, and co-occurrence of author keywords based on a bibliometric analysis of 137 publications extracted from the Scopus database between 2004 and September 2021. This research examines and elaborates the kind and direction of research on Halal cosmetics undertaken over the last few decades. It also identifies the most influential writers, journals, institutions, and countries concerning Halal cosmetics. This study might provide academics and practitioners with detailed insights into the Halal cosmetics concepts, which can subsequently be used as a reference for strategic efforts. AbstrakArtikel ini menerapkan analisis bibliometrik untuk mengkaji karya dan literatur yang ada tentang kosmetik halāl untuk mengeksplorasi perjalanan konsep yang berkembang sejak kemunculannya. Penelitian ini menggunakan pendekatan bibliometrik seperti sitasi, co-citation, dan co-occurrence 137 publikasi yang diambil dari database Scopus antara tahun 2004 dan September 2021. Penelitian ini mengkaji dan menguraikan jenis dan arah penelitian tentang kosmetik halāl yang dilakukan selama beberapa dekade terakhir serta mengidentifikasi penulis, jurnal, institusi, dan negara paling berpengaruh tentang kosmetik halāl. Analisis SWOT singkat termasuk dalam penelitian ini. Kajian ini memberikan wawasan yang mendetail kepada akademisi dan praktisi tentang konsep kosmetik halāl, yang selanjutnya dapat digunakan sebagai referensi untuk upaya-upaya strategis.